Mathematical modeling with differential equations - Mickens, Ronald E., 1943- (Boca Raton : Chapman & Hall/CRC Press, 2022)
"Mathematical Modeling with Differential Equations aims to introduce various strategies for modeling systems using differential equations. Some of these methodologies are elementary and quite direct to comprehend and apply while others are complex in nature and require thoughtful, deep contemplation. Many topics discussed in the chapter do not appear in any of the standard textbooks and this provides users an opportunity to consider a more general set of interesting systems that can be modeled. For example, the book investigates the evolution of a "toy universe," discusses why "alternate futures" exists in classical physics, constructs approximate solutions to the famous Thomas-Fermi equation using only algebra and elementary calculus, and examines the importance of "truly nonlinear" and oscillating systems. Features -- Introduces, defines, and illustrates the concept of "dynamic consistency" as the foundation of modeling -- Can be used as the basis of an upper-level undergraduate course on general procedures for mathematical modeling using differential equations -- Discusses the issue of dimensional analysis and continually demonstrates its value for both the construction and analysis of mathematical modeling"--
Includes bibliographical references and index.
Keywords: Differential equations; Mathematical models; Mathematical analysis